Incidence of Ct scan-detected pulmonary embolism in patients with oncogene-addicted, advanced lung adenocarcinoma. Issue 5 (November 2015) - Verso, Melina; Chiari, Rita; Mosca, Stefano; Franco, Laura; Fischer, Matthias; Paglialunga, Luca; Bennati, Chiara; Scialpi, Michele; Agnelli, Giancarlo
Abstract: Background: Patients with stage IIIB-IV lung adenocarcinoma are at high-risk for pulmonary embolism (PE). In these patients, EGFR and KRAS mutations as well as EML4/ALK rearrangements are recognized as "drivers" and as targets for therapy. Data on the incidence of PE in oncogene-addicted lung cancer patients are limited. Aims: The aims of this study were to evaluate the incidence of CT scan-detected PE in patients with stage IIIB-IV lung adenocarcinoma and to assess the potential correlation between the presence of these oncogenes and the PE risk. Methods: Baseline staging or re-staging chest contrast-enhanced CT scans of patients with stage IIIB-IV lung adenocarcinoma were retrospectively reviewed and adjudicated for the presence of PE. Data on the oncogene drivers (EGFR, KRAS or EML4/ALK) of the same patients were collected. Results: A total of 173 patients with lung adenocarcinoma were included in the study. 24.8% of patients were EGFR mutated (31/125), 21.6% were KRAS mutated (27/125) and 13.6% hadan EML4/ALK rearrangement (17/125). 41 patients had a CT-detected PE (23.7%). A PE was observed in 5 patients with EGFR mutation (16.2%), in 5 patients with KRAS mutation (18.5%), in 8 patients with ELM4/ALK mutation (47.1%). The presence of ELM4/ALK rearrangement was associated with an increased risk of PE [HR:2.06 (95%CI 1.08- 3.55)]. Risk of PE was not found to be associated with EGFR or KRAS mutations. Conclusions: Patients with advanced lung adenocarcinoma were at high risk for PE. The presence of EML4/ALK rearrangement was associated with an increased PE risk. Highlights: Patients with advanced lung cancer are reported to be at high risk for VTE. The expression of specific oncogene drivers is known for patients with advanced lung cancer. We found a correlation between ELM4/ALK and incidence of PE in lung cancer patients. ELM4/ALK could be used to identify patients with lung cancer at very high risk for PE. In these cancer patients an antithrombotic prophylaxis could be proposed